Polymer nanoparticles from low-energy nanoemulsions for biomedical applications - Grijalvo, Santiago; Rodriguez-Abreu, Carlos (Beilstein Journal of Nanotechnology, 2023)
The formulation of nanoemulsions by low-energy strategies, particularly by the phase inversion composition method, and the use of these nanoemulsions as templates for the preparation of polymer nanoparticles for biomedical applications are reviewed. The methods of preparation, nature of the components in the formulation, and their impact on the physicochemical properties, drug loading, and drug release are discussed. We highlight the utilization of ethyl cellulose, poly(lactic-co-glycolic acid), and polyurethane/polyurea in the field of nanomedicine as potential drug delivery systems. Advances are still needed to achieve better control over size distribution, nanoparticle concentration, surface functionalization, and the type of polymers that can be processed.
Keywords: ethyl cellulose; nanoemulsions; nanomedicine; phase inversion composition (PIC) method; PLGA; polymer nanoparticles; polyuria; polyurethane; surfactants